The AtProT family. Compatible solute transporters with similar substrate specificity but differential expression patterns - Grallath, Silke; Weimar, Thilo; Meyer, Andreas; Gumy, Christophe; Suter-Grotemeyer, Marianne; Neuhaus, Jean-Marc; Rentsch, Doris (My University, 2005)
Proline transporters (ProTs) mediate transport of the compatible solutes Pro, glycine betaine, and the stress-induced compound gamma-aminobutyric acid. A new member of this gene family, AtProT3, was isolated from Arabidopsis (Arabidopsis thaliana), and its properties were compared to AtProT1 and AtProT2. Transient expression of fusions of AtProT and the green fluorescent protein in tobacco (Nicotiana tabacum) protoplasts revealed that all three AtProTs were localized at the plasma membrane. Expression in a yeast (Saccharomyces cerevisiae) mutant demonstrated that the affinity of all three AtProTs was highest for glycine betaine (K-m = 0.1-0.3 mM), lower for Pro (K-m = 0.4-1 mM), and lowest for gamma-aminobutyric acid (K-m = 4-5 mM). Relative quantification of the mRNA level using real-time PCR and analyses of transgenic plants expressing the beta-glucuronidase (uidA) gene under control of individual AtProT promoters showed that the expression pattern of AtProTs are complementary. AtProT1 expression was found in the phloem or phloem parenchyma cells throughout the whole plant, indicative of a role in long-distance transport of compatible solutes. beta-Glucuronidase activity under the control of the AtProT2 promoter was restricted to the epidermis and the cortex cells in roots, whereas in leaves, staining could be demonstrated only after wounding. In contrast, AtProT3 expression was restricted to the above-ground parts of the plant and could be localized to the epidermal cells in leaves. These results showed that, although intracellular localization, substrate specificity, and affinity are very similar, the transporters fulfill different roles in planta.
Keywords: AMINO-ACID TRANSPORTERS; ARABIDOPSIS-THALIANA; PROLINE ACCUMULATION; BARLEY LEAVES; DELTA(1)-PYRROLINE-5-CARBOXYLATE SYNTHETASE; FUNCTIONAL-CHARACTERIZATION; QUATERNARY AMMONIUM; AMINOBUTYRIC-ACID; GLYCINE-BETAINE; ORGANIC SOLUTES